The Content of Vitamin C and E on Seaweed Porridge Eucheuma cottonii and Turbinaria conoides - Yanuarti, Rini; Nurjanah, Nurjanah; Anwar, Effionora; Pratama, Ginanjar (Marinade, 2018)
Seaweed was a source of vitamin C and E. They were an antioxidant contained in seaweed. The objective of this study was to determine of vitamins (C and E) in the seaweed porridge of E. cottonii and T. conoides were thought to have potential as raw material for making sunscreen cream. The methods were included total microbial analysis, vitamin C and E analysis on seaweed porridge. The results of a total microbial assay on E. cottonii was 8,7x103 colony/g while on T. conoides was 3,5x104 colony/g. They were the safe category of microbial test. The content of vitamin C on E. cottonii and T. conoides (1: 1) on seaweed porridge was 0,07 mg/100 gram, while vitamin E content obtained is 10 mg/100 gram.